An airline yield management simulation model with multiple fare classes allowing cancellation, no-show and chance passengers with an assessment of different booking policies - Villanueva, Aissa Mae P. (Animo Repository, 2005)
This study is primarily based on a single leg flight with multiple fare classes that allows cancellations, no shows and chance passengers with an assessment of the different booking policies, such as the non nested seat allocation, nested booking limit, and overbooking policy. he main objectives of the study are to identify and assess the distinguishing effects of the different booking policies, which include the non nested seat allocation approach, nested booking limit and overbooking policy, reviewed from the literature to revenue, and to ascertain how variations of customer behavior variables, identified as the inter-arrival time of the regular passengers, cancellation probabilities, no show probabilities and chance passengers arrival distribution, affect the revenue across the different booking policies. At the same time, the impact of the interaction of these policies and customer behavior variables to the revenue to be generated in the system will be determined.